The association of two genetic markers and evaluation scores for tölt in Icelandic horses - Barry, Ida (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2016)
Previous studies have shown that some horse breeds carries a mutated variant of the gene DMRT3, which is crucial for horses to perform alternative gaits like pace and tölt. The mutation is also important for harnessing racing performance. A previous unpublished genome wide association study found that two SNP (single nucleotide polymorphism) markers on chromosome 13 (22,296,211 bp) and 28 (35,485,344 bp) were significantly associated with the estimated breeding values (EBV) for tölt. They could possibly have an effect on the quality of slow tölt and tölt. The aim of this current study was to follow up the previous findings in additional Icelandic horses. We used 95 five-gaited Icelandic horse mares that were all shown at a breeding field test between the ages of 5 and 6. Hair samples were selected from the Animal Genetics Laboratory, Swedish University of Agricultural Sciences, Uppsala, Sweden. The DNA was prepared with the Chelex procedure, and the horses were genotyped for two SNPs on chromosome 13 (22,296,211 bp) and chromosome 28 (35,485,344 bp). The SNP genotyping was performed with the StepOnePlus Real-Time PCR System using custom designed TaqMan SNP Genotyping Assays. When it came to genotype frequencies for the SNP marker on chromosome 13, the dominating allele was T with 64 % frequency. For the SNP marker on chromosome 28, the dominating allele was A with 83 % frequency. The study showed no significant associations between the SNP markers on chromosome 13 and chromosome 28 and the evaluation score of tölt and slow tölt.